Information technology tools influnce on knowledge sharing practices: A case study among students of Faculty Administrative Science & Policy Studies UiTM Melaka City Campus / Norliza Yacob and Sheera Nabila Singar - Yacob, Norliza; Singar, Sheera Nabila (Faculty of Administrative Science and Policy Studies, 2014)
According to Davenport and Prusak (1998), knowledge is combination of experiences, opinion of the expert, values, contextual information which being converted into new information or idea. It was embedded in the mind of the people and uses by people every day.Besides that, in the organization, knowledge was embedded not only in the document, but also in the routine, process, practices and norms. Knowledge sharing is one mechanism in knowledge. Knowledge sharing becomes the one of the important components either in the organization, lower and higher learning institution, instructor or even in our countries. Individuals are free to share their knowledge without limitation. According to Goh (2012), knowledge sharing can be described as the activities that involve of transfer of information between two or more people. It was the process of exchange of information to innovate something new such as new idea, new product and new solutions.